ARTIFICIAL INTELLIGENCE (AI)-BASED ASSESSMENT: A TRANSFORMATIVE ENGLISH EDUCATION CURRICULUM - Benni Ichsanda Rahman Hz; Ammamiarihta Ammamiarihta (Universitas Duta Bangsa Surakarta, 2025)
Artificial Intelligence (AI) has been developing at a fast pace and is increasingly embedded in everyday human activities. In the realm of education AI serves as a transformative force, reshaping both teaching practices and learning processes. A key contribution of AI in this context lies in its capacity to deliver individualized and adaptive learning experiences. This study aims to develop an Artificial Intelligence (AI)-based English learning assessment system in the English Education program at the State Islamic University of North Sumatra, Medan. The study also seeks to measure the extent to which the AI-based assessment curriculum has effectively achieved the program's vision, mission, objectives, and graduate profile. A qualitative case study within purposive sampling approach was employed to select participants who had relevant experience and knowledge in English teaching and learning. The data collection methods included Focused Group Discussions (FGDs) with 20 lecturers and 100 students, as well as in-depth interviews with lecturers. The data from questionnaire were analyzed to identify patterns, trends, and differences in the responses of the respondents. The findings of this study indicate that the use of AI in assessing English proficiency among students has proven to be effective and efficient, not only in individual assessment but also in supporting the evaluation of academic program curricula. However, the findings also highlight the need for adequate technological readiness and training for both lecturer and student to optimize AI utilization.